2018
DOI: 10.1088/1361-648x/aacd6c
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional tight-binding approach for metal clusters, nanoparticles, surfaces and bulk: application to silver and gold

Abstract: Density-functional based tight-binding (DFTB) is an efficient quantum mechanical method that can describe a variety of systems, going from organic and inorganic compounds to metallic and hybrid materials. The present topical review addresses the ability and performance of DFTB to investigate energetic, structural, spectroscopic and dynamical properties of gold and silver materials. After a brief overview of the theoretical basis of DFTB, its parametrization and its transferability, we report its past and recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 307 publications
1
27
0
Order By: Relevance
“…In the present work, we have used the Density Functional based Tight Binding (DFTB) scheme 57,58 , in its second order formulation (also known as Self-Consistent Charge DFTB 59 ), to compute the potential energy surfaces for neutral, anionic and cationic gold and silver clusters. In a previous work 60,61 , we adapted (see supplementary materials for more details) existing gold 62 and silver parameters 63 and validated their use to properly model these metals from cluster to bulk sizes. The exploration of the PES has been done using a Parallel-Tempering Molecular Dynamics (PTMD) scheme 64 , as implemented in the deMonNano code 65,66 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the present work, we have used the Density Functional based Tight Binding (DFTB) scheme 57,58 , in its second order formulation (also known as Self-Consistent Charge DFTB 59 ), to compute the potential energy surfaces for neutral, anionic and cationic gold and silver clusters. In a previous work 60,61 , we adapted (see supplementary materials for more details) existing gold 62 and silver parameters 63 and validated their use to properly model these metals from cluster to bulk sizes. The exploration of the PES has been done using a Parallel-Tempering Molecular Dynamics (PTMD) scheme 64 , as implemented in the deMonNano code 65,66 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…As shown in the Figure 1 been found comparable to the DFT values. 36 Therefore, the GNP structures obtained from DFTB geometry optimizations are likely to be reliable.…”
Section: Methodology a Structuresmentioning
confidence: 99%
“…Oliveira et al 35 have conducted a benchmark of the Au-Au parameters for a series of gold clusters against DFT. These parameters have been used in different studies to determine the properties of gold and silver clusters, nanoparticles and bulk, 36 the role of surface charge on the orientation of water at the interface for the application in electrodes, 37 and the interaction between gold clusters and biomolecules. 38 These various theoretical approaches have definitely provided valuable insights into the interfacial interaction between gold surfaces and water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The TBDFT approach has empirical parameters, but can maintain close-to-DFT accuracy, for considerably reduced computational cost [95]. Hence, provided it is used within the region of parameterization, DFTB can be an efficient method for metal cluster GO, which was recently shown for TBDFT applications to silver and gold clusters [96]. A study has also been reported which combines TBDFT and DFT directly in the GO of gold clusters [97].…”
Section: Global Optimization Methods For Metal Clusters and Nanoalloysmentioning
confidence: 99%
“…Clusters of noble metal elements are of considerable research interest, due to their intriguing optical properties and promising applications in catalysis and other technologies. Gold shows unique physical and chemical properties, which are significantly influenced by relativistic effects [11,29,88,90,92,96,103,107,109,111]. There have been several GO studies on gold clusters using EPs followed by DFT relaxation [164][165][166].…”
Section: Au Clustersmentioning
confidence: 99%